Aplikasi Tagihan Air Artesis Berbasis Web Dengan Sms Gateway Pada Perumahan Classica Permata Puri Semarang - Putri Altria, Hutrimas Arimbi, Nurgiyatna, S.T., M.Sc., Ph.D (2017)
Needed for water is the important thing in every activity of our life as a human being. Same as happened in houses Permata Puri Classica Semarang. For making this needed of potable water fulfilled, so this community used Artesis water machine. But some problem of managing datas that related to payment process and billing process of every water that used by this community appear. To make it easier for this community in houses Permata Puri Classica Semarang, then a water bills system payment web based with SMS Gateway additional features was made. This water bills system payment programmed using PHP, HTML and use MySQL as database. This water bills system payment have made easier every activity that related to this water services and everyone in houses Permata Puri Classica Semarang that using this water services for manage data of people that uses this water service, data of bill, rationing the bills, and paperless and aving memory.